2020
DOI: 10.3390/ani10030422
|View full text |Cite
|
Sign up to set email alerts
|

Challenging a Myth and Misconception: Red-Light Vision in Rats

Abstract: Simple Summary: Light substantially influences animal physiology and behavior. Thus, it is a prerequisite to house laboratory animals under optimal light conditions. Different species possess different sets of photoreceptors, resulting in differential perception of the visible-light spectrum. While humans are trichromats with red-, green-and blue-sensitive cones, rats and mice are dichromats possessing ultraviolet-and green-sensitive cones. This led to the common assumption that red light is invisible to roden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 32 publications
(45 reference statements)
0
11
0
Order By: Relevance
“…This study reinforced the already existing notion that red light is experienced as a total absence of usable light. In contrast, another study (Niklaus et al, 2020) showed significant scotopic and photopic ERG responses to red light even at low intensities. In the present study we challenge the notion of form vision blindness under red light and find, contrary to expectation, good behavioral performance.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…This study reinforced the already existing notion that red light is experienced as a total absence of usable light. In contrast, another study (Niklaus et al, 2020) showed significant scotopic and photopic ERG responses to red light even at low intensities. In the present study we challenge the notion of form vision blindness under red light and find, contrary to expectation, good behavioral performance.…”
Section: Introductionmentioning
confidence: 77%
“…Rodents lack red cones ( Deegan and Jacobs, 1993 ; Jacobs et al, 1991 ; Szél and Röhlich, 1992 ), but from the inability to see red as a color, it does not necessarily follow that they cannot absorb red light through their rod-dominated retina to support form vision. A recent study ( Niklaus et al, 2020 ) examined the retinal responses mediated by rods and cones of pigmented (Brown Norway) and albino (Wistar) rats in response to monochromatic far-red light of 656 ± 10 nm in both photopic (light-adapted) and scotopic (dark-adapted) settings. Both rat strains showed significant scotopic and photopic ERG responses to red light even at low intensities.…”
Section: Discussionmentioning
confidence: 99%
“…1D; Video 1). Rodents are typically assumed not to see red light (De Farias Rocha et al, 2016); though some evidence contradicts this (Nikbakht & Diamond, 2021;Niklaus et al, 2020), we never observed any behavioral response to red light (little of which likely reaches the eyes when applied to the hind paw), suggesting that the aiming phase does not provide mice any visual cue about the forthcoming photostimulus. Reflectance of red light off the paw is measured by the adjacent photodetector (red trace).…”
Section: Resultsmentioning
confidence: 58%
“…But from the inability to see red as a color, it does not necessarily follow that rodents cannot absorb red light through their rod-dominated retina to support form vision. A recent study (Niklaus et al, 2020) examined the retinal responses mediated by rods and cones of pigmented (Brown Norway) and albino (Wistar) rats in response to monochromatic far red light of 656 ± 10 nm in both photopic (light-adapted) and dark-adapted (scotopic) settings. Both rat strains showed significant scotopic and photopic ERG responses to red light even at low intensities.…”
Section: Discussionmentioning
confidence: 99%